Sub-Saharan African Challenge Program: Internal Review Report - Mokwunye, U; Ellis-Jones, J. (Forum for Agricultural Research in Africa, 2010)
The objective of this internal review was to analyze the progress made by the SSA CP as described in the Medium Term Plan of the respective Pilot Learning Sites and to evaluate the possible need for reorienting the programme coordination at different levels in the coming year, which is the concluding year of the Programme‟s research phase.